Analisis Akuntansi Forensik Terhadap Dugaan Korupsi Pengadaan Chormebook Kemendikbudristek Tahun 2025 - Macella Aullia Jayadi; Ayu Asari; Tries Ellia Sandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Public procurement of educational technology represents a strategic government investment but remains highly vulnerable to corruption risks. This study examines the role of forensic accounting in analyzing alleged corruption in the 2025 Chromebook procurement at the Ministry of Education, Culture, Research, and Technology. Using a qualitative descriptive approach based on literature review, this study integrates fraud theories, forensic accounting techniques, investigative audit practices, and public procurement governance frameworks. The analysis reveals that weaknesses in procurement planning, internal control, and oversight create opportunities for fraud, including price mark-up, collusion, and manipulation of procurement documentation. Forensic accounting, supported by investigative audits, audit trail control, whistleblowing mechanisms, and big data analytics, enhances the detection and evidentiary strength of corruption cases. The findings also emphasize that transparency, accountability, auditor competence, and technological integration are essential components in preventing procurement fraud and strengthening law enforcement processes. This study highlights forensic accounting as a strategic anti-corruption instrument that not only supports legal proof but also contributes to sustainable improvements in public procurement governance.